2020
DOI: 10.13181/mji.oa.193494
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior affects cardio-metabolic risk in high school teenagers in a developing country

Abstract: BACKGROUND Modernization negatively changes lifestyle, characterized by excessive eating and reduced energy consumption, and concurrently increases the cardiometabolic risk. This study was aimed to evaluate the association between eating behavior and cardio-metabolic risk factors including body mass index (BMI) in percentile, blood pressure (BP) in percentile, waist circumference, and heart rate in total subjects and gender sub-groups. METHODS This analytical cross-sectional study was done from July to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This is in contrast to the previous finding by Cronin and his colleagues, who found that women were more likely to consume low-calorie food, fruits and carbonated drinks, whereas men reported frequent consumption of meat, dietary products and carbohydrate- rich foods [ 12 ]. Numerous studies indicate that females reported to be more vulnerable to restrained, uncontrolled, and emotional eating behaviors leading to cardio and metabolic risk [ 14 , 49 , 52 ]. However, there is a significant gender difference for two dimension of EBP i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the previous finding by Cronin and his colleagues, who found that women were more likely to consume low-calorie food, fruits and carbonated drinks, whereas men reported frequent consumption of meat, dietary products and carbohydrate- rich foods [ 12 ]. Numerous studies indicate that females reported to be more vulnerable to restrained, uncontrolled, and emotional eating behaviors leading to cardio and metabolic risk [ 14 , 49 , 52 ]. However, there is a significant gender difference for two dimension of EBP i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum number of samples is calculated with software from the web "the sample size calculator" (https://clincalc.com/stats/samplesize.aspx) with one study group vs. population design and the dichotomous data as the primary endpoint. The incidence population of the study parameter was 18% (Esfahani et al, 2016;WHO, 2021) and the incidence study group was 27.1% (Suhadi et al, 2020). We set α 0.05, β 0.2, power 0.8, and got a minimal sample of 153 respondents.…”
Section: Methodsmentioning
confidence: 99%